Fishing for feed in China: Facts, impacts and implications. Issue 1 (24th October 2019) - Zhang, Wenbo; Liu, Min; Sadovy de Mitcheson, Yvonne; Cao, Ling; Leadbitter, Duncan; Newton, Richard; Little, David C.; Li, Songlin; Yang, Yi; Chen, Xiao; Zhou, Wei
Abstract: China is the world's largest capture fisheries and aquaculture producer. Over recent decades, China's domestic marine catch composition has changed markedly, from large volumes of a few high‐valued food species to multiple, small, low‐valued, species, a significant proportion of which is primarily used as animal, especially fish, feed. Despite the growing volume and economic importance of the feed catches, their species composition, catch volumes and socio‐environmental impacts are all poorly understood. Based on a nationwide survey of >800 fishing vessels, and the identification and measurement of >12, 000 fish and invertebrate individuals, the present study provides an overview of the feed component of China's domestic marine catch, by volumes, species and sizes, and found it to be substantial and biologically unsustainable. Half of the trawler catch (3 million metric tons, mmt), or 35% of the total catch (4.6 mmt) in China's exclusive economic zone, are now comprised of low‐valued "feed‐grade fish". The present study identified 218 fish species, 50 crustaceans and five cephalopods, and of these, 102 fish species were food species with 89% individuals in their juvenile size ranges. Feed‐grade fish were mainly used as aquaculture feed directly, or indirectly, through the feed industry after reduction to fishmeal and fish oil. The unparalleled scale and poor fisheries resource condition of China's domestic marine fisheries, in parallel with severe overfishing of juveniles, creates a demand for fundamental changes to fishery management practices, including a significant reduction of fishing effort to ensure productivity and ecosystem resilience.